Digital technology and multimodal medical image processing in a research laboratory - KANDARAKI, ASPASIA (Neusis, 2024)
This article is based on a laboratory study and deals with the digitization work of histopathology images and the creation of regions of interest (ROI), in a research laboratory developing computer aided diagnostic systems (Computer Aided Diagnosis-CAD). The primary material has been drawn from the collaborative practice of an Assistant Professor of Biomedical Engineering and a PhD Candidate regarding the creation of regions of interest. In particular, in the article I examine how, during a collaborative work aiming to create regions of interest, the scientists understand, shape, and classify their experimental data, through the engagement of their bodies with digital technology. For my analysis, I rely on a multimodal approach that combines analytical tools of Conversation Analysis (CA), developed by the anthropologist Charles Goodwin. I also draw from studies in the field of Science and Technology Studies (STS) that focus on the multimodal character of research practice. I argue that it is not the digital technology that produces the image processing but the way laboratory researchers are working with digital technology while simultaneously adapting to the technology in use. I also show that the researchers' work is embodied, with the analysis of the medical image being produced, indexically, even by dint of the specific way the researchers' bodies are positioned.